Measurement of Saumlaki Community Health Center Service Quality Using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) - Salakory, Hans Sammy Marthin; Matulessy, Febby Sonya; Lating, Zulfikar; Ibrahim, Ilyas (Jurnal Dunia Kesmas, 2025)
Public Health Center is the frontline of health care services in Indonesia, both for individuals and communities. Public Health Center plays an important role in achieving the highest level of health for the community. Ideally, Public Health Center should be able to provide excellent service to the public, thereby providing maximum satisfaction. In reality, the services provided by Public Health Center of Saumlaki to the public do not fully meet patient expectations and there are still weaknesses that lead to complaints and dissatisfaction among patients. This study was developed to determine the level of satisfaction of the community in the working area of Public Health Center of Saumlaki towards the services provided. The analytical technique used is the servqual method with the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) approach. The results of the analysis showed that the CSI value was 76.41%, which means that patients are satisfied with the services provided. The IPA value shows 80.47% for the Tangibles (Physical Facilities) dimension, 77.97% Reliability (Reliability), 79.56% Responsiveness (Responsiveness), Assurance (Assurance) of 82.38%, Empathy (Empathy) of 81.47%. With an average value of 80.37%, which means that the dimensions of service quality in the patient's perception are less satisfied.